Cationic Biphotonic Lanthanide Luminescent Bioprobes Based on Functionalized Cross‐Bridged Cyclam Macrocycles. Issue 10 (7th April 2020) - Mendy, Jonathan; Thy Bui, Anh; Roux, Amandine; Mulatier, Jean‐Christophe; Curton, Damien; Duperray, Alain; Grichine, Alexei; Guyot, Yannick; Brasselet, Sophie; Riobé, François; Andraud, Chantal; Le Guennic, Boris; et al.
Abstract: Cationic lanthanide complexes are generally able to spontaneously internalize into living cells. Following our previous works based on a diMe‐cyclen framework, a second generation of cationic water‐soluble lanthanide complexes based on a constrained cross‐bridged cyclam macrocycle functionalized with donor‐π‐conjugated picolinate antennas was prepared with europium(III) and ytterbium(III). Their spectroscopic properties were thoroughly investigated in various solvents and rationalized with the help of DFT calculations. A significant improvement was observed in the case of the Eu 3+ complex, while the Yb 3+ analogue conserved photophysical properties in aqueous solvent. Two‐photon (2P) microscopy imaging experiments on living T24 human cancer cells confirmed the spontaneous internalization of the probes and images with good signal‐to‐noise ratio were obtained in the classic NIR‐to‐visible configuration with the Eu 3+ luminescent bioprobe and in the NIR‐to‐NIR with the Yb 3+ one. Abstract : Cationic two‐photon europium and ytterbium luminescent bioprobes based on a cross‐bridged cyclam macrocycle functionalized by a charge‐transfer antenna show spontaneous internalization in living cells.